The anomalous atmospheric structure of the strongly magnetic Ap star HD 166473. Issue 2 (28th September 2020) - Järvinen, S P; Hubrig, S; Mathys, G; Khalack, V; Ilyin, I; Adigozalzade, H
ABSTRACT: High-resolution spectropolarimetric observations of the strongly magnetic, superslowly rotating rapidly oscillating Ap star HD 166473 are used to investigate the implications of the presence of a variable strong magnetic field on the vertical and surface horizontal distribution of various chemical elements. The analysis of the calculated least-squares deconvolution Stokes I and V profiles confirms the previously reported detection of non-uniform horizontal surface distribution of several chemical elements. To test the vertical abundance stratification of iron peak and rare earth elements, magnetic field measurements were carried out using spectral lines of these elements belonging to neutral and ionized stages. We find clear indication of the existence of a relation between the magnetic field strength and its orientation and vertical element stratification: magnetic field values obtained for elements in different stages close to the magnetic equator are rather similar, whereas the dispersion in field strengths is remarkably large in the regions close to magnetic field poles. At the phases of negative and positive extrema the mean longitudinal field strength determined from the analysis of the rare-earth element lines is usually stronger than when using Fe and Cr. The strongest mean longitudinal magnetic field, up to −4160 ± 226 G, is detected using the La ii line list at the negative extremum, followed by the measurements using the Pr iii lines with 〈 Bz 〉=−3740 ± 343 G and the Ce ii lines with 〈 Bz 〉 = −3372 ± 247 G. The strongest mean longitudinal magnetic field of positive polarity, up to 3584 ± 354 G is detected using the Pr iii lines, followed by the measurement 〈 Bz 〉 = 2517 ± 249 G using the Ce ii lines.